Randomized Trial of Metformin With Anti-Tuberculosis Drugs for Early Sputum Conversion in Adults With Pulmonary Tuberculosis. (26th November 2021) - Padmapriydarsini, Chandrasekaran; Mamulwar, Megha; Mohan, Anant; Shanmugam, Prema; Gomathy, N S; Mane, Aarti; Singh, Urvashi B; Pavankumar, Nathella; Kadam, Abhijeet; Kumar, Hemanth; Suresh, Chandra; Reddy, Devaraju; et al.
Abstract: Background: Metformin, by reducing intracellular Mycobacterium tuberculosis growth, can be considered an adjunctive therapy to anti-tuberculosis treatment (ATT). We determined whether metformin with standard ATT reduces time to sputum culture conversion and tissue inflammation in adults with pulmonary tuberculosis (PTB). Methods: In a randomized, 8-week, clinical trial, newly diagnosed, culture-positive PTB patients were randomized to standard ATT (HREZ = control arm) or standard ATT plus daily 1000 mg metformin (MET-HREZ = Metformin with Rifampicin [METRIF] arm) for 8 weeks during 2018–2020 at 5 sites in India. The primary end point was time to sputum culture conversion by liquid culture during 8 weeks of ATT. Plasma inflammatory markers were estimated in a subset. A Cox proportional hazard model was used to estimate time and predictors of culture conversion. Results: Of the 322 patients randomized, 239 (74%) were male, and 212 (66%) had bilateral disease on chest radiograph with 54 (18%) showing cavitation. The median time to sputum culture conversion by liquid culture was 42 days in the METRIF arm and 41 days in the control arm (hazard ratio, 0.8; 95% confidence interval [CI], .624–1.019). After 8 weeks of ATT, cavitary lesions on X-ray (7, 5.3% vs 18, 12.9%; relative risk, 0.42; 95% CI, .18–.96; P  = .041) and inflammatory markers were significantly lower in the METRIF arm. Higher body mass index and lower sputum smear grading were associated with faster sputum culture conversion. Conclusions: The addition of metformin to standard ATT did not hasten sputum culture conversion but diminished excess inflammation, thus reducing lung tissue damage as seen by faster clearance on X-ray and reduced inflammatory markers. Clinical Trials Registration: Clinical Trial Registry of India (CTRI/2018/01/011176) Abstract : The addition of metformin to anti-tuberculosis therapy does not affect sputum conversion. However, it brings about early closure of cavities and decreases inflammation in the lungs secondary to tuberculosis and, thus, may favor faster recovery and decreased lung tissue damage.